PENGGUNAAN MEDIA FOTO UNTUK MENINGKATKAN MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD - Miladiyanti, Meidina Faradila; Tahir, M.; Istiningsih, Siti (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2018)
This is a new author guidelines and article template of Jurnal Ilmiah Widya Pustaka Pendidikan edition January 2021 publication. Abstract is written briefly and factually using Times New Roman letter, size 10 pt with text length between 200-250 words. English version abstracts are written in English in past tense and in good sentences. Do not use abbreviations or citation in the abstract. Results and conclusions are written in present tense. Abstract includes background of problems, research objectives, research methods, results and conclusionThis research was motivated by the low student learning outcomes so that research was conducted at this school. This research is included in the classroom action research which aims to improve student learning outcomes in natural science subjects in class III SDN 35 Ampenan 2017/2018 Academic Year, with the use of photo media students are expected to understand the material described by the teacher and stimulate students' understanding of the material that. This research was conducted in 2 cycles, each cycle consisted of 2 meetings and was carried out through four stages: planning, implementation, observation and evaluation, and reflection. The research instruments are observation sheets, learning outcomes and documentation. Observer in this study was one person, namely: class III teacher. And the results of the study showed that the average student learning outcomes in the first cycle were 69.58 with kelaksikal completeness which was 46% while the students' activity acquisition scores were 32 which were categorized as less active and teacher 14 activity scores were in good category. In the second cycle there was an increase with an average value of 80.83 students with 83.3% classical completeness, while the student activity acquisition score was 42 with the active category and the teacher activity was 18 with very good categories. This means that Classroom Action Research (CAR) has fulfilled the indicator that you want to achieve. Therefore, based on the results of the study it can be concluded that, the use of photo media can improve science learning outcomes for third grade students of SDN 35 Ampenan 2017/2018 Academic Year.